Identification of Bacterial Soft Rot in Potatoes From Batu City, Indonesia - Berliana, Sonia; Abadi, Abdul Latief; Aini, Luqman Qurata; Yusnawan, Eriyanto (Universitas Panji Sakti, 2025)
Soft rot is a plant disease that can reduce both the quality and quantity of potato production, primarily caused by the Pectobacterium carotovorum. This study aims to isolate and identify the bacteria responsible for soft rot disease in potato tubers using molecular methods. Bacterial isolation was performed on a diseased potato tuber collected from Sumber Brantas Village, followed by a pathogenicity test, PCR, 16S rRNA gene sequencing, and phylogenetic analysis. Based on macroscopic and microscopic examination, four isolates exhibiting soft rot symptoms were identified: P1, P2, K5, and K7. The 16S rRNA sequencing results and BLAST analysis showed that isolate K5 was closely related to Serratia rubidaea, isolate P2 was closely associated with Pectobacterium carotovorum, isolate P1 was closely related to Pseudomonas koreensis, and isolate K7 was closely associated with Ralstonia pseudosolanacearum. This study presents the first molecular characterization of bacteria responsible for soft rot in potato tubers originating from Batu City, East Java. The findings provide foundational insights that may support the development of molecular-based diagnostic tools and region-specific disease management strategies for potato cultivation in Indonesia.